Cimahi elementary school teachers' perceptions of differentiated learning - Sandry Adhitya; Dinn Wahyudin; Erda Ilma Herfia (Himpunan Pengembang Kurikulum Indonesia, 2025)
Teachers' deep understanding of differentiated learning will make its implementation more effective in meeting the diverse needs of students. The success of differentiated learning also depends on teachers' ability to plan, implement, and evaluate learning. Therefore, it is important to know teachers' perceptions related to understanding differentiated learning as a basis for optimizing the implementation of student-focused learning. Based on this background, this study aims to analyze teachers' perceptions of differentiated learning, focusing on understanding the purpose, content, process, and evaluation of learning. This research also explores the extent to which teachers understand and implement differentiated learning and the obstacles faced. The method used is descriptive, with data collected through questionnaires to 52 elementary school teachers in Cimahi City using a random sampling technique. Data analysis was conducted to calculate the percentage and average score. The results showed that teachers' perceptions of differentiated learning were in the high category, with a good understanding of learning objectives, content, strategies, and evaluation. However, improvement in understanding, especially in mastering differentiated learning strategies, is still needed. Continuous online and offline training and utilizing the Platform Merdeka Mengajar can support the implementation of the Kurikulum Merdeka more effectively. Abstrak Pemahaman guru yang mendalam mengenai pembelajaran terdiferensiasi akan menjadikan implementasinya lebih efektif dalam memenuhi keragaman kebutuhan siswa. Kesuksesan pembelajaran terdiferensiasi pun tergantung pada kemampuan guru dalam merencanakan, melaksanakan, dan mengevaluasi pembelajaran. Oleh karena itu, penting untuk mengetahui persepsi guru terkait pemahaman pembelajaran terdiferensiasi sebagai dasar untuk mengoptimalkan pelaksanaan pembelajaran yang berfokus pada siswa. Berdasarkan latar belakang tersebut, penelitian ini bertujuan untuk menganalisis persepsi guru terhadap pembelajaran terdiferensiasi dengan fokus pada pemahaman tujuan, isi, proses, dan evaluasi pembelajaran. Penelitian ini juga menggali sejauh mana guru memahami dan menerapkan pembelajaran terdiferensiasi serta kendala yang dihadapi. Metode yang digunakan adalah deskriptif, dengan data dikumpulkan melalui kuesioner kepada 52 guru sekolah dasar di Kota Cimahi menggunakan teknik sampling acak. Analisis data dilakukan untuk menghitung persentase dan skor rata-rata. Hasil penelitian menunjukkan persepsi guru terhadap pembelajaran terdiferensiasi berada pada kategori tinggi, dengan pemahaman yang baik tentang tujuan, isi, strategi, dan evaluasi pembelajaran. Namun, peningkatan pemahaman, terutama dalam menguasai strategi pembelajaran terdiferensiasi, masih dibutuhkan. Pelatihan berkelanjutan, baik secara online maupun offline, serta pemanfaatan Platform Merdeka Mengajar, dapat mendukung penerapan Kurikulum Merdeka secara lebih efektif. Kata Kunci: kurikulum merdeka; pembelajaran terdiferensiasi; persepsi guru